Representations of rectilinear light propagation in the thinking of 12-13 year olds: A transformative teaching intervention - Grigorovitch, Alyona (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2021)
This research investigates the transformation of the seventh-grade students' mental representations of the rectilinear propagation of light. The researcher employed the quasi-experimental method on two groups of students aged 12-13 years. The survey involved 102 students who were divided into two equal groups determined by the stratified sampling technique. The first group participated in a didactic intervention based on the students' representations. The second group of students participated in a traditional school teaching. The Mann–Whitney U test was utilized for calculating the significance of the data. The statistical analysis showed that the pretest and the posttest progress was statistically significant for the first group. It resulted in the mental constitution of a representation that is compatible with the scientific model.The research results allow the design of effective interventions for the teaching of light propagation and geometric optics in general.